Radiological signs in osteopetrosis - Kumar, Nitish; Singh, Tanya (International Journal of Contemporary Pediatrics, 2023)
Osteopetrosis, or marble bone disease, is a rare genetic metabolic bone disease initially described by Albers-Schönberg in 1904. Osteopetrosis includes a clinically heterogeneous group of conditions characterized by increased bone density due to a defect in bone resorption by osteoclasts. The osteoclasto-genesis as well as the osteoclastic activity may be distorted. Clinical symptoms of osteopetrosis vary greatly in their presentation and severity as the spectrum ranges from the neonatal onset with life-threatening complications to incidental findings of osteopetrosis on radiographs. Diagnosis is based on clinical and radiographic evaluation, confirmed by bone biopsy and genetic testing. Treatment depends on the symptoms and severity of the disease and requires a multidisciplinary team approach.